The Influence of Financial Knowledge, Income, and Lifestyle on Real Asset Investment Decisions among Police Officers at Sanggau Police Department, Sanggau Regency - Ramadanti, Aulia; Hariyanto, Dedi; Safitri, Heni (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of financial literacy, income, and lifestyle on real asset investment decisions among police officers at the Sanggau Police Department. The research employed a quantitative associative method involving 150 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results show that financial literacy, income, and lifestyle have a positive and significant effect on investment decisions. The regression equation obtained is Y = 1.070 + 0.155X₁ + 0.254X₂ + 0.297X₃, with R = 0.623 and R² = 0.388. The F-test (F = 26.137; sig = 0.000) and t-tests confirmed that all three variables significantly affect investment decisions. These findings indicate that strong financial literacy, stable income, and prudent lifestyle choices encourage rational investment behavior. Future research should include variables such as digital literacy, financial confidence, or investment motivation to broaden the understanding of individual investment behavior.